Melanocytoma of the optic disc – a case report - Sharma, H; Puri, L R (Nepalese Journal of Ophthalmology, 2012)
Introduction: Melanocytoma of the optic disc is a benign lesion. Objective: To describe a case of optic disc melanocytoma Case: A 48-year old lady presented with gradual visual impairment associated with a floater. The right eye fundus examination showed a mass uniformly dark black in colour on the optic disc. The mass completely obscured the fluorescence on fluorescein angiography and was thus differentiated from malignant melanoma. Conclusion: Optic disc melanocytoma can present with visual impairment and a floater. Fluorescein angiography can be useful to differentiate between malign DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6553 Nepal J Ophthalmol 2012; 4 (2): 323-325